Strengthening Santri Engagement with Turats for SDGs: The Role of IRE Teachers - Muhammad Rizqi; Muhammad Isa Anshory; Edwards Geraldine (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to examine and understand the strategic role of Islamic Religious Education teachers in increasing interest in reading classical books in students at the Imam Bukhari Islamic Boarding School in Karanganyar, particularly in supporting the achievement of the SDGs through quality and inclusive religious education. Theoretical framework: this study is based on the theory of the role of educators as facilitators, motivators, and mentors in religious education, as well as the concept of learning interests in the context of traditional Islamic education aligned with SDGs principles. Literature review: includes a study of the importance of classical books in the pesantren tradition, the challenges of modernization of the reading culture of students, and the role of teachers in facilitating religious learning within the framework of SDGs-based education. Method: used a qualitative approach with a descriptive method, where data is collected through observation, in-depth interviews with teachers and students, and documentation of learning activities. Results: research shows that teachers have a central role in fostering students' interest through a personal approach, strengthening religious values, integrating traditional and modern teaching methods, and providing consistent motivation to support sustainable educational development. Teachers also contribute to creating a conducive learning atmosphere and establishing close relationships with students. Implications: these findings emphasize the importance of training and strengthening the capacity of teachers to carry out their role effectively in the preservation of classical Islamic literature and the formation of students’ character in line with SDGs Goal 4 (Quality Education). Novelty: This study emphasizes integrative strategies carried out by Islamic Religious Education teachers in the context of modern Islamic boarding schools contributing to SDGs discourse, which have not been widely revealed in previous studies.